2021
DOI: 10.1088/1742-6596/1935/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Success factors in product development projects: expert opinions

Abstract: Successful product development is a common challenge for technical and management experts. The increasing pressure on time reduction and cost savings while enhancing product features, requires rethinking project management methods. This paper analyses the opinions of product development experts about the success factors of product development projects. A voluntary online survey was used for data collection in 2020. The study confirms that development engineers, test engineers, project managers, and product dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…'Soft' factors of projects such as communication and collaboration are appreciated. A former study among product development experts (Soltész and Berényi 2021) found the importance of teamwork, project manager's control, and other factors of success that allow flexibility and responses to the uncertainty of the project. However, a well-defined project goal is among the most important success factors next to these.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…'Soft' factors of projects such as communication and collaboration are appreciated. A former study among product development experts (Soltész and Berényi 2021) found the importance of teamwork, project manager's control, and other factors of success that allow flexibility and responses to the uncertainty of the project. However, a well-defined project goal is among the most important success factors next to these.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms the need for managing uncertainty (Szabó and Cserháti 2013). However, literature on product development success (González and Palacios 2002;Cooper 2019) reflect the even more agile approach and highlights the strategic focus, communication, team skills, knowledge management, and other soft factors, and a survey among product development experts (Soltész and Berényi 2021) confirmed that beyond that adherence to stability, setting clear project goals is given a high weight. A clearly written set of project goals, as a specification or scope, was evaluated as the most important success factor, followed by the collaboration of the project team.…”
mentioning
confidence: 99%